Renal transplantation and obstructive uropathy - Meneses, Rejane de Paula; Hallusch, Cecília; Carmes, Eliane Ribeiro (Brazilian Journal of Transplantation, 2004)
Introduction: Obstructive uropathy is a common etiology of end stage renal disease in infancy and childhood. A clinical-surgical protocol that aims for reconstruction of the urinary tract before transplantation has been considered fundamental in the graft prognosis. Objective: to compare graft function and survival in patients with and without uropathies and to describe outcomes in patients with augmented bladder. Methods: we studied 62 kidney transplanted patients from 1990 to 2000, in “Hospital Pequeno Principe de Curitiba”, Parana, Brazil, with more than 6 months of follow-up; 32 (51,6%) with uropathy. All have been submitted to urological evaluation before and after transplantation. Results: fifty eight percent of the 62 patients were male, age of 12,1±4 years (mean±standard deviation). Comparing uropathic and non-uropathic patients, there was no significant difference in relation to sex, age, mortality, living or cadaver donor, compatibility, acute rejection, chronic graft nephropathy, graft loss and creatinine clearance during the follow-up. Urinary tract infection ocurred only in the group with uropathies. Among those with urological disorder, previous unilateral nephrectomy was done in 8,6% and bilateral in 82,8%, bladder augmentation was done in 37,1% and continent conduit in 45,7%. Urodynamic studies showed a significant difference in the bladder capacity and compliance before and after augmentation and after transplant. Those who had undergone augmentation did not have more vesicoureteral reflux or lithiasis, but had more urinary tract infection and hydronephrosis. Conclusion: specific pre-transplantation and follow-up clinical-surgical protocols for children with obstructive uropathy was related with a favorable evolution and with good renal graft prognosis.